Kinematic Comparison of Orthopedic Shoes and Ankle-Foot Orthoses in Children With Cerebral Palsy - Andrey A. Koltsov; Andrey Yu. Aksenov; Elnur I. Dzhomardly (Travmatologiâ i Ortopediâ Rossii, 2022)
Background. In patients with cerebral palsy (CP), secondary orthopedic deformities and violations of the walking pattern are often observed, so various methods of treatment are used for its correction, including orthosis. Abroad, orthoses (AFO) for ankle joints are most often used in clinical practice, whereas in Russia complex orthopedic shoes are used. At the same time, there are no comparative studies investigating the influence of these orthopedic products on the biomechanical parameters of gait.